Population-based study of surgical treatment with and without tumour resection in patients with locally recurrent rectal cancer. Issue 6 (18th February 2019) - Westberg, K; Palmer, G; Hjern, F; Holm, T; Martling, A
Abstract: Background: Population-based studies of treatment of locally recurrent rectal cancer (LRRC) are lacking. The aim was to investigate the surgical treatment of patients with LRRC at a national population-based level. Methods: All patients undergoing abdominal resection for primary rectal cancer between 1995 and 2002 in Sweden with LRRC as a first event were included. Detailed information about treatment, complications and outcomes was collected from the medical records. The patients were analysed in three groups: patients who had resection of the LRRC, those treated without tumour resection and patients who received best supportive care only. Results: In all, 426 patients were included in the study. Of these, 149 (35·0 per cent) underwent tumour resection, 193 (45·3 per cent) had treatment without tumour resection and 84 (19·7 per cent) received best supportive care. Abdominoperineal resection was the most frequent surgical procedure, performed in 65 patients (43·6 per cent of those who had tumour resection). Thirteen patients had total pelvic exenteration. In total, 63·8 per cent of those whose tumour was resected had potentially curative surgery. After tumour resection, 62 patients (41·6 per cent) had a complication within 30 days. Patients who received surgical treatment without tumour resection had a lower complication rate but a significantly higher 30-day mortality rate than those who underwent tumour resection (10 versus 1·3 per cent respectively; P = 0·002). Of all patients included in the study, 22·3 per cent had potentially curative treatment and the 3-year survival rate for these patients was 56 per cent. Conclusion: LRRC is a serious condition with overall poor outcome. Patients undergoing curative surgery have an acceptable survival rate but substantial morbidity. There is room for improvement in the management of patients with LRRC. Graphical Abstract: This population-based study investigated treatment and outcome in a national cohort of patients with locally recurrent rectal cancer. One-third of all 426 patients underwent tumour resection, and abdominoperineal resection was the most common surgical procedure. Some 22·3 per cent of all patients had potentially curative surgery. R0 resection best hope of cure